Heroic diplomacy : Sadat, Kissinger, Carter, Begin and the quest for Arab-Israeli peace - Stein, Kenneth W., 1946- (Routledge, 1999)
Heroic Diplomacy provides an unequalled insight into the internal divisions and untold stories of the peace process, covering an extraordinary range of first-hand accounts.
Keywords: Arab-Israeli conflict -- 1973-1993.; Arab-Israeli conflict -- Diplomatic history.; Diplomatic negotiations in international disputes.; Arab countries -- Foreign relations -- Israel.; Israel -- Foreign relations -- Arab countries.; Israel-Arab War, 1973 -- Peace.; Arab-Israeli conflict -- 1993- -- Peace.; Conflit israélo-arabe -- 1973-1993.; Conflit israélo-arabe -- Histoire diplomatique.; Négociations diplomatiques dans les conflits internationaux.; États arabes -- Relations extérieures -- Israël.; Israël -- Relations extérieures -- États arabes.; Guerre israélo-arabe, 1973 -- Paix.; Conflit israélo-arabe -- 1993- -- Paix.; HISTORY -- General.; Peace; Arab-Israeli conflict; Arab-Israeli conflict -- Diplomatic history; Arab-Israeli conflict -- Peace; Diplomatic negotiations in international disputes; Diplomatic relations; Arab countries; Israel; Since 1973